Araucaria angustifolia: desenvolvimento de técnica de pós-colheita para aumento de vida útil do pinhão e análise da sua cultura alimentar e identidade territorial - Rimoli, Pedro Augusto Resende (2024)
This thesis addresses the importance of the pine nut and the araucaria tree in the southern region of Brazil, with a focus on the state of Paraná. It highlights their role in the local diet, culture, and economy, and discusses the use of hydrothermal treatment and its consequent analysis through sensory evaluation. The pine nut is considered a significant seasonal symbol, with harvesting and commercialization mainly occurring from May to June, while the araucaria is recognized as an emblematic tree that plays a crucial role in preserving regional biodiversity. However, this species faces significant challenges, including predatory exploitation and the impacts of climate change. The research emphasizes the need for more effective environmental protection policies to ensure the conservation of these natural resources and contribute to the sustainable development of local communities. Furthermore, the thesis discusses the situation of Araucaria angustifolia, also known as the Paraná pine, a native species of Brazil found primarily in the southern region. This tree plays fundamental roles in maintaining biodiversity and the regional economy, especially through the production of pine nuts. However, it faces threats such as logging and habitat fragmentation, requiring urgent conservation actions. Investments in scientific research and public policies are essential to develop evidence-based conservation strategies and promote sustainable forest management practices. Finally, the thesis presents empirical research on pine nut conservation techniques, highlighting the importance of hydrothermal treatment in maintaining its qualities during storage. The experiments conducted revealed that treatment at 50 ºC provided good results in terms of the physical-chemical, sensory, and sanitary characteristics of the pine nut. The thesis also advocates for greater investment in the various forms of presenting this food. These results contribute not only to the scientific understanding of conservation processes but also to the cultural and environmental appreciation of the pine nut and Araucaria angustifolia in the context of sustainable rural development.